Edmund Gurney's evolutionary anti-Wagnerism. Issue 4 (3rd April 2021) - Anderson, Timothy
ABSTRACT: Amidst a resurgence of critical interest in Richard Wagner's music, Alain Badiou has claimed that historical debating about Wagner forms a distinctive 'genre' of philosophical polemic; a distinctive sociology of art that 'became systematically negative from a certain point onwards'. Yet Badiou apprehends in his study only a narrow canon of texts in critical theory. The present article tests Badiou's claims by exploring Wagner's early anglophone reception. It outlines a parallel 'genre' of politically engaged Wagnerian polemic in nineteenth century Britain, recovering how Wagner's cult-like popularity suggested new kinds of social reform to thinkers like the evolutionist Edmund Gurney (1847–88). This article first establishes the epochal curiosity about Wagner's political potential. It reintroduces George Bernard Shaw's socialist reading of der Ring des Nibelungen and related controversies about Wagner's political biography. Then it examines how Gurney, even before the emergence of these socialist interpretations, derived a programme of reform from a critique of Wagner's utopian idea of a 'people's art'. By emphasising the connectedness of Gurney's anti-Wagnerism and his 'philanthropy', this article argues that Gurney suggests new ways of answering Badiou's concern about the genre's historical failure to convert its social critique into a praxis.